Exploring the potential use of artificial intelligence in the Indonesian broadcasting industry - Sjuchro, Dian Wardiana; Sugiana, Dadang; Nurfauziah, Isni; Tri, Nguyen Minh (Faculty of Communications Science, Dr. Soetomo University, 2025)
AI is a system designed to help work become more effective and efficient. In the broadcasting industry, AI is mentioned as having potential that deserves attention. This study examined the adoption of AI in Indonesia’s broadcasting industry, addressing the research gap in emerging markets by analysing its operational impacts and ethical risks. Through a descriptive qualitative, alongside systematic reviews of Scopus, Web of Science, and Garuda databases, this research identified how Indonesia’s unique media landscape shapes AI integration. The findings revealed that while AI enhances efficiency, its ethical challenges necessitate localised solutions, leading to a proposed ‘Dual Accountability Model’, which reduces violations by 31% by balancing automation with human oversight. These results urge policymakers to develop KPI-certified AI governance frameworks and provide broadcasters with strategies for the ethical implementation of AI, offering a replicable model for ASEAN nations navigating similar technological transitions.